Circulating Platelet-Derived Microparticles Associated with Postdischarge Major Adverse Cardiac Events in ST-Elevation Acute Myocardial Infarction - Anggoro Budi Hartopo; Dyah Samti Mayasari; Ira Puspitawati; Hasanah Mumpuni (Cardiology Research and Practice)
Introduction. Platelet-derived microparticles (PDMPs) measurement adds prognostic implication for ST-elevation acute myocardial infarction (STEMI). The long-term implication of PDMPs in STEMI needs to be corroborated. Methods. The research design was a cohort study. Subjects were STEMI patients and were enrolled consecutively. The PDMPs were defined as microparticles bearing CD41(+) and CD62P(+) markers detected with flow cytometry. The PDMPs were measured on hospital admission and 30 days after discharge. The outcomes were major adverse cardiac events (MACE), i.e., a composite of cardiac death, heart failure, cardiogenic shock, reinfarction, and resuscitated ventricular arrhythmia, occurring from hospitalization until 1 year after discharge. Results. We enrolled 101 subjects with STEMI. During hospitalization, 17 subjects (16.8%) developed MACE. The PDMPs were not different between subjects with MACE and those without (median (IQR): 3305.0/μL (2370.0–14690.5/μL) vs. 4452.0/μL (2024.3–14396.8/μL), p=0.874). Forty-five subjects had increased PDMPs in 30 days after discharge as compared with on-admission measurement. Subjects with increased PDMPs had significantly higher 30-day MACE as compared to subjects with decreased PDMPs 17 (37.8%) vs. 6 (16.7%, p=0.036). There was a trend toward higher MACE in subjects with increased PDMPs as compared to those with decreased PDMPs in 90 days after discharge (48.9% vs. 30.6%, p=0.095) and 1 year after discharge (48.9% vs. 36.1%, p=0.249). Conclusion. The PDMPs level was increased from the day of admission to 30 days after discharge in patients with STEMI. The persistent increase in the PDMPs level in 30 days after the STEMI event was associated with the 30-day postdischarge MACE and trended toward increased MACE during the 90-day and 1-year follow-up.